Primary Tooth Enamel Loss After Manual and Mechanical Microabrasion - Cilense Zuanon, Angela Cristina [UNESP]; Santos-Pinto, Lourdes Aparecida Martins dos [UNESP]; Azevedo, Elcilaine Rizzato [UNESP]; Lima, Luciana Monti [UNESP] (Amer Acad Pediatric Dentistry, 2008)
Purpose: This study's purpose was to assess the amount of dental enamel loss on primary incisors after manual or mechanical microabrasion with a phosphoric acid/pumice poste. Methods: Ten exfoliated primary maxillary incisors were bisected faciolingually and the resulting 20 halves were randomly assigned to 2 groups: group 1 (N=10) manual technique (plastic spatula); and group 2 (N=10) mechanical technique (rubber cup attached to a low-speed handpiece). Microabrasion was performed on the buccal surface using an abrasive paste prepared with 37% phosphoric acid and pumice. Ten 20-second applications alternated with 20-second risings were performed in each group. Enamel thickness measurements made under stereomi-croscopy before and after microabrasion were analyzed statistically by analysis of variance and pairwise t test. Results: There was a statistically significant difference (P=.003) between the manual and mechanical techniques. The mechanical technique produced a mean enamel loss of 274.16 mu m (66% of total enamel thickness), while the mean enamel loss with the manual technique was 152.59 mu m (39% of total enamel thickness). Conclusion: Manual microabrasion using a plastic spatula removed less enamel, but was sufficient to eliminate most superficial stains and defects, and may be a viable option for the microabrasive technique on primary teeth. (Pediatr Dent 2008;30:420-3) Received March 15, 2007 / Lost Revision September 19, 2007 / Revision Accepted October 19, 2007
Keywords: MICROABRASION; DENTAL ENAMEL; PRIMARY TEETH